2020
DOI: 10.3847/1538-4357/ab62ad
|View full text |Cite
|
Sign up to set email alerts
|

Metallicity and α-Element Abundance Gradients along the Sagittarius Stream as Seen by APOGEE

Abstract: Using 3D positions and kinematics of stars relative to the Sagittarius (Sgr) orbital plane and angular momentum, we identify 166 Sgr stream members observed by the Apache Point Observatory Galactic Evolution Experiment (APOGEE) that also have Gaia DR2 astrometry. This sample of 63/103 stars in the Sgr trailing/leading arm is combined with an APOGEE sample of 710 members of the Sgr dwarf spheroidal core (385 of them newly presented here) to establish differences of 0.6 dex in median metallicity and 0.1 dex in [… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
58
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 99 publications
8
58
2
Order By: Relevance
“…The presence of spatial [α/Fe] variations in Local Group dwarf galaxies, such as MW dwarf spheroidal satellite galaxies and the Magellanic Clouds (e.g., Kirby et al 2011;Nidever et al 2020), has generally not been quantified, thus largely precluding comparisons of observational expectations for [α/Fe] gradients to the GSS. The exceptions include chemical abundance studies of M31 satellite dwarf galaxies (Vargas et al 2014b), where no strong evidence for significant [α/Fe] gradients was found, and Sgr (Hayes et al 2020). Hayes et al measured an [α/Fe] gradient of (0.1 − 1.2) × 10 −3 dex deg −1 (or 0.06−0.15 dex in absolute difference) between the Sgr core and Sgr streams-in addition to weaker internal [α/Fe] gradients in the streamsthat they interpreted as reflecting Sgr's [Fe/H] gradient combined with the characteristic anticorrelation between [α/ Fe] and [Fe/H] in dwarf galaxies (e.g., Shetrone et al 2001;Venn et al 2004;Kirby et al 2011).…”
Section: Implications For the Gss Progenitormentioning
confidence: 99%
See 3 more Smart Citations
“…The presence of spatial [α/Fe] variations in Local Group dwarf galaxies, such as MW dwarf spheroidal satellite galaxies and the Magellanic Clouds (e.g., Kirby et al 2011;Nidever et al 2020), has generally not been quantified, thus largely precluding comparisons of observational expectations for [α/Fe] gradients to the GSS. The exceptions include chemical abundance studies of M31 satellite dwarf galaxies (Vargas et al 2014b), where no strong evidence for significant [α/Fe] gradients was found, and Sgr (Hayes et al 2020). Hayes et al measured an [α/Fe] gradient of (0.1 − 1.2) × 10 −3 dex deg −1 (or 0.06−0.15 dex in absolute difference) between the Sgr core and Sgr streams-in addition to weaker internal [α/Fe] gradients in the streamsthat they interpreted as reflecting Sgr's [Fe/H] gradient combined with the characteristic anticorrelation between [α/ Fe] and [Fe/H] in dwarf galaxies (e.g., Shetrone et al 2001;Venn et al 2004;Kirby et al 2011).…”
Section: Implications For the Gss Progenitormentioning
confidence: 99%
“…For the LMC, SMC, and M33, radial metallicity gradients of −(0.06-0.08) dex kpc −1 have been detected out to several disk scale lengths (LMC: Choudhury et al 2016;SMC: Dobbie et al 2014;Parisi et al 2016;Choudhury et al 2018;M33: Kim et al 2002;Tiede et al 2004;Barker et al 2007) that are similar to the gradient in the MW's disk (−0.06 dex kpc −1 ; e.g., Cheng et al 2012;Hayden et al 2014). In addition, metallicity differences of 0.4-0.6 have been observed between the Sgr core and Sgr streams (Chou et al 2007;Monaco et al 2007;Keller et al 2010;Hayes et al 2020), which translate to an intrinsic gradient of about −0.2 dex kpc −1 in the Sgr progenitor based on dynamical modeling (Law & Majewski 2010). 8 Although only weak internal gradients are measured along the Sgr streams ((−1.2−(−1.4)) × 10 −3 dex deg −1 , but consistent with zero within the uncertainties; Hayes et al 2020), combining these measurements with modeling provides evidence for a gradient with dynamical age (i.e., initial orbital radius; −0.12 ± 0.03 dex Gyr −1 ) in the Sgr progenitor.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though this is in fact the main tenet of the popular sub-field of Astrophysics known as Galactic Archaeology, not many such forensic studies are currently on record. Large numbers of detailed chemical abundances have so far only been collected and analysed for two stellar halo structures: the Sagittarius stream (see Monaco et al 2007;Chou et al 2007;de Boer et al 2015;Carlin et al 2018;Hayes et al 2020) and the Gaia Sausage (see Nissen & Schuster 2010;Helmi et al 2018;Mackereth et al 2019;Vincenzo et al 2019;Molaro et al 2020;Feuillet et al 2020). Additionally, a small number of stars in globular cluster streams have been under the magnifying glass of high-resolution spectroscopy (e.g.…”
Section: Introductionmentioning
confidence: 99%